Filling the gaps of dinosaur eggshell phylogeny: Late Jurassic Theropod clutch with embryos from Portugal - Araújo, Ricardo (2013)
The non-avian saurischians that have associated eggshells and embryos are represented only by the sauropodomorph Massospondylus and Coelurosauria (derived theropods), thus missing the basal theropod representatives. We report a dinosaur clutch containing several crushed eggs and embryonic material ascribed to the megalosaurid theropod Torvosaurus. It represents the first associated eggshells and embryos of megalosauroids, thus filling an important phylogenetic gap between two distantly related groups of saurischians. These fossils represent the only unequivocal basal theropod embryos found to date. The assemblage was found in early Tithonian fluvial overbank deposits of the Lourinhã Formation in West Portugal. The morphological, microstructural and chemical characterization results of the eggshell fragments indicate very mild diagenesis. Furthermore, these fossils allow unambiguous association of basal theropod osteology with a specific and unique new eggshell morphology.